Optimasi Proses Penggaraman dan Pengeringan Ikan Nike Asin Kering dengan Metode Response Surface Method: Study of the Influence of Salt Concentration and Drying Time on Characteristics of Dried Salted Largesnout Goby (Awaous melanocephalus) - Reinal Putalan; Septian Palma Ariany; Afriani Kasadi; Taufik Hidayat (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Largesnout goby (Awaous melanocephalus) is an endemic and potential fish species that is spread in Sulawesi. One of the processed fish products is dried salted fish. This study aims to determine the effect of salt concentration and duration of salting on the characteristics of dry salted Nike fish (Awaous melanocephalus). Through organoleptic testing of hedonic quality which includes appearance, smell, taste, texture and protein content. Making salted fish using dry salting method with a salt concentration of 5%, and 10% with a drying time of 5, 6 and 7 hours. The test results were analyzed sensory using the Kruskal Wallis method. Protein content was analyzed using a factorial completely randomized design with three replications, as well as optimization of the processing of dried salted fish on protein content using the Response Surface Method (RSM). Salt concentration and drying time had a significant effect on the protein characteristics of salted fish. Dry salted nike fish has an organoleptic value of 7-9. The chemical composition of the highest protein Nike fish protein is 25.28%. Optimization of the salting and drying process on protein content using the Response Surface Method was obtained at a salt concentration of 10% and a drying time of 7 hours.